Achieving external validity in home advantage research: generalizing crowd noise effects - Myers, Tony D. (Frontiers in Psychology, 2014)
Different factors have been postulated to explain the home advantage phenomenon in sport. One plausible explanation investigated has been the influence of a partisan home crowd on sports officials' decisions. Different types of studies have tested the crowd influence hypothesis including purposefully designed experiments. However, while experimental studies investigating crowd influences have high levels of internal validity, they suffer from a lack of external validity; decision-making in a laboratory setting bearing little resemblance to decision-making in live sports settings. This focused review initially considers threats to external validity in applied and theoretical experimental research. Discussing how such threats can be addressed using representative design by focusing on a recently published study that arguably provides the first experimental evidence of the impact of live crowd noise on officials in sport. The findings of this controlled experiment conducted in a real tournament setting offer a level of confirmation of the findings of laboratory studies in the area. Finally directions for future research and the future conduct of crowd noise studies are discussed.